Multisensory reading promotion in academic libraries - Yu, Wenyan; Jiang, Yiping; Wu, Yanqi; Cheng, Yanxia (Frontiers in Psychology, 2023)
To confront college students’ new reading patterns and the continuous decline in academic library borrowing rates, we conducted empirical research on promoting multisensory reading as a way to attract students’ attention, and to stimulate interest in, and promote the practice of, reading through a library program called “Reading Today Listening Everyday” (RTLE) on a library’s WeChat public account. The multisensory mode was proven to be effective in promoting library reading with a high number of tweeted page views and an increased borrowing rate for recommended books. In 2020, 269 issues accompanied by 269 audio frequencies garnered 80,268 page views, depending on the caliber of the reading promoter out of the 48 librarians and 52 student anchors behind it. The 484 RTLE-recommended books were borrowed 113 times in 2020, which was a rate 1.46 times higher than in 2019 (77 times). To explicate the relationship between tweet views and borrowing rates for recommended books, statistical results showed that more page views indicate greater reader interest, leading to increased borrowing. From readers’ feedback and comments, the gain afforded by multisensory reading can improve higher-level reading trends such as the number of reading interests, enjoyment, engagement, etc. Our results are designed to provide a new mode for improving library reading promotion with the expectation of meeting readers’ needs and increasing library collection utilization rates. Additionally, the experience of multisensory reading promotion allows librarians to innovate when providing reading services and serves as a reference for reading promotion for other libraries, businesses, and policy-planning offices.